Anti-β2-Glycoprotein I and Anti-Prothrombin Antibodies in Antiphospholipid-Negative Patients with Thrombosis - Previtali, Sara; Barbui, Tiziano; Galli, Monica (Thrombosis and Haemostasis, 2002)
We performed a case-control study to assess whether anti-β2-glycoprotein I and anti-prothrombin antibodies are independent risk factors of thrombosis. Cases were 79 patients with arterial and/or venous thrombosis without lupus anticoagulants, anticardiolipin antibodies and systemic lupus erythematosus; controls were 85 normal subjects. The prevalences and titers of IgG and IgM anti-β2-glycoprotein I and antiprothrombin antibodies were similar in both groups. Cases were analyzed with respect to the arterial or venous type of thrombosis and to the presence of congenital or acquired risk factors for thrombosis: no statistically significant relationships with the presence of anti-β2glycoprotein I and anti-prothrombin antibodies were found. Our data indicate that anti- β2-glycoprotein I and anti-prothrombin antibodies are not risk factors for thrombosis independent of lupus anticoagulants and anticardiolipin antibodies. Their measurement, therefore, is not warranted in the laboratory screening of patients with arterial and/or venous thrombosis.
Keywords: Antiphospholipid antibodies; anti-β2-glycoprotein I antibodies; antiprothrombin antibodies; thrombosis; casecontrol study